Performing without pressure? The effect of ghost games on effort- and skill-based tasks in the football Bundesliga - Christoph Bühren; Dominic Jung (Philipps-University Marburg, School of Business and Economics, 2022)
We analyze the natural experiment of ghost games in the 2019/2020 season of the German football Bundesliga and confirm previous studies showing that the home advantage diminishes if the stadium is empty. However, our paper is the first that distinguishes between effort- and skill-based tasks in this setting. In line with behavioral economics, we observe that a supportive audience has a positive effect on effort-based performance but a negative effect on some offensive skill-based performance measures.
Keywords: C93; Z20; 330; Ghost games; home advantage; effort vs; skill; Covid-19